Molded body and method for manufacturing the same

By integrating polypropylene with controlled crystallization into fiber-reinforced resin compositions and using a resin sheet, the method addresses the issue of surface unevenness in molded articles, achieving smoother and more aesthetically pleasing parts with reduced thickness.

JP7601780B2Active Publication Date: 2024-12-17IDEMITSU UNITECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021551473
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-03
Filing Date
2020-10-02
Publication Date
2024-12-17
Estimated Expiration
2040-10-02

AI Technical Summary

Technical Problem

Fiber-reinforced resins used in automotive parts suffer from surface unevenness due to fiber lifting, which is exacerbated by the use of covering sheets, leading to impaired appearance and increased thickness, making it difficult to achieve both aesthetic improvement and weight reduction.

Method used

Incorporating polypropylene with a specific crystallization rate into fiber-reinforced resin compositions, forming a uniform skin layer with oriented fibers, and using a resin sheet with controlled crystallization to promote smoothness, thereby enhancing the appearance of molded articles.

Benefits of technology

The method results in fiber-reinforced resin molded articles with improved surface smoothness and appearance, reducing unevenness and thickness while maintaining strength and rigidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601780000003
    Figure 0007601780000003
  • Figure 0007601780000004
    Figure 0007601780000004
  • Figure 0007601780000005
    Figure 0007601780000005
Patent Text Reader

Abstract

This molded body comprises: a molded body base including a polypropylene and a fibrous reinforcing material; and a resin sheet containing at least a resin layer and covering at least a portion of the surface of the molded body base, wherein the polypropylene has a crystallization rate of at least 0.6 min-1 at 135°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molded article and a method for producing the same. [Background technology]

[0002] In the fields of automobiles and motorcycles, the shift from metal to resin as a component material has been considered in order to reduce weight. Fiber-reinforced resins containing glass, carbon fiber, etc. are sometimes used as resin materials to obtain the same strength, rigidity, and low linear expansion coefficient as metal parts. However, fiber-reinforced resins have a problem in that unevenness caused by fibers appears on the surface of the molded product, which is called fiber lifting, which impairs the appearance.

[0003] As a method for improving the appearance of fiber-reinforced resin, a method of covering the surface of a part made of fiber-reinforced resin with a sheet has been investigated (for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-158481 A [Patent Document 2] JP 2010-260251 A Summary of the Invention

[0005] However, it is difficult to improve the appearance even if the sheet is used, and there are cases where it may even worsen the appearance, so there is an even greater demand for technology to improve the appearance of fiber-reinforced resin. In addition, the technology of Patent Document 1 aims to improve the appearance by sandwich molding a decorative sheet, a fiber-free resin, and a fiber-containing resin, but there are problems such as the thickness of the molded body becoming large, the weight reduction effect being lost, and restrictions being placed on the shape of the molded body. With the technology of Patent Document 2, particularly when the molded body is formed by injection molding, it is not possible to expect an improvement in appearance.

[0006] An object of the present invention is to provide a fiber-reinforced resin molding having an excellent appearance.

[0007] The present inventors have considered the reason why the appearance cannot be improved even if the above-mentioned covering sheet (surface sheet) is used as follows. That is, since the fibers are randomly present in the fiber-reinforced resin, the distance between the surface sheet and the fibers varies depending on the location. This difference in distance causes unevenness in the amount of shrinkage of the matrix resin made of fiber-reinforced resin, which generates unevenness on the sheet surface and impairs the surface smoothness, i.e., the appearance. Here, when the fiber-reinforced resin is injection molded toward a mold, the side in contact with the mold is cooled and a so-called "skin layer" with a low crystallinity is formed. In the skin layer, the fibers are oriented in the flow direction, so the distance between the sheet surface and the fibers is easily made uniform. However, when the surface sheet is used, the skin layer is not sufficiently formed in the fiber-reinforced resin due to the insulating effect of the surface sheet, and the proportion of the so-called "core layer" with random fiber orientation increases, which promotes differences in the distance from the fibers and increases the formation of unevenness on the sheet surface, resulting in a loss of appearance. The inventors discovered that by using a polypropylene having a specific crystallization rate as the polypropylene contained in the fiber-reinforced resin, the formation of a skin layer in the fiber-reinforced resin is promoted, resulting in a molded body having high surface smoothness and an excellent appearance, and thus completed the present invention.

[0008] According to the present invention, the following molded body and the like are provided. 1. A molded body including polypropylene and a fibrous reinforcing material; A resin sheet including at least a resin layer and covering at least a part of a surface of the molded body; Including, The crystallization rate of the polypropylene at 135°C is 0.6 min -1 The above is a molded body. 2. The crystallization rate of the polypropylene at 135°C is 1.0 min -1 2. The molded article according to 1, which is as described above. 3. The molded article according to 1 or 2, wherein the resin layer in the resin sheet contains polypropylene. 4. The crystallization rate of the polypropylene contained in the resin layer at 130°C is 2.5 min -1 4. The molded body according to claim 3, which is: 5. The molded article according to 3 or 4, wherein the isotactic pentad fraction of the polypropylene contained in the resin layer is 80 mol % or more and 99 mol % or less. 6. The molded article according to any one of 3 to 5, wherein the content of the nucleating agent in the polypropylene contained in the resin layer is 1.0% by mass or less of the resin layer. 7. The molded product according to any one of 3 to 6, wherein the polypropylene contained in the resin layer does not contain a nucleating agent. 8. The molded body according to any one of 1 to 7, wherein the resin sheet includes a printed layer on the molded body side as viewed from the resin layer. 9. The resin sheet includes an easy-adhesion layer on the molded body side as viewed from the resin layer, 9. The molded article according to any one of 1 to 8, wherein the easy-adhesion layer contains at least one selected from the group consisting of a urethane resin, an acrylic resin, a polyolefin, and a polyester. 10. The resin sheet includes an undercoat layer located on the molded body side as viewed from the resin layer, and a metal layer laminated on the molded body side as viewed from the undercoat layer, the undercoat layer comprises one or more resins selected from the group consisting of urethane resins, acrylic resins, polyolefins, and polyesters, 10. The molded product according to any one of 1 to 9, wherein the metal layer contains one or more metal elements selected from the group consisting of tin, indium, chromium, aluminum, nickel, copper, silver, gold, platinum, and zinc. 11. Placing a resin sheet on the mold; and Crystallization speed at 135℃ is 0.6min -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the resin sheet, and the resin sheet is shaped to fit a mold while the molding resin composition and the resin sheet are integrated. 11. A method for producing the molded article according to any one of 1 to 10, comprising: 12. Shaping the resin sheet to fit the mold; and Crystallization speed at 135℃ is 0.6min -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the shaped resin sheet, thereby integrating the molding resin composition with the resin sheet. 11. A method for producing the molded article according to any one of 1 to 10, comprising: 13. Heating a molding resin composition containing polypropylene and a fibrous reinforcing material so that the polypropylene melts; Supplying the heated molding resin composition onto a resin sheet placed in a mold; and The molding resin composition is cooled and solidified on the resin sheet to obtain a molded body including a molded body main body made of the solidified molding resin composition and the resin sheet covering at least a part of a surface of the molded body. Including, The crystallization rate of the polypropylene contained in the molding resin composition subjected to the melting at 135° C. is 0.6 min -1 That's all. A method for producing a molded body.

[0009] According to the present invention, it is possible to provide a fiber-reinforced resin molding having an excellent appearance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a molded body according to one embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing a molded body according to another embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram of an apparatus used for producing a resin sheet in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (Molded body) A molded article according to one aspect of the present invention includes a molded article body and a resin sheet. The molded article body includes polypropylene and a fibrous reinforcing material. The resin sheet includes at least a resin layer and covers at least a part of the surface of the molded article body. The crystallization rate of the polypropylene included in the molded article body at 135°C is 0.6 min -1 The molded article according to one aspect of the present invention has the above-mentioned configuration, and thus has a surface of the molded article, i.e., the resin sheet surface, which has high smoothness and excellent appearance.

[0012] In the molded article according to one embodiment of the present invention, the crystallization rate of polypropylene at 135°C is 0.6 min -1 By the above, the solidification temperature of the molding resin composition (fiber-reinforced resin) supplied to form the molded body during injection molding is increased, and solidification is accelerated. When such a fiber-reinforced resin is supplied onto a resin sheet, the formation of a skin layer on the resin sheet side of the fiber-reinforced resin is promoted. In such a skin layer, the fibrous reinforcing material is oriented in the flow direction (parallel to the resin sheet). Therefore, by forming a thicker skin layer, the distance between the surface of the resin sheet and the fibrous reinforcing material in the fiber-reinforced resin is made more uniform, surface unevenness due to the difference in shrinkage of the resin is alleviated, and a molded body (fiber-reinforced resin molded body) with excellent surface smoothness is obtained. The terms "skin layer" and "core layer" are names for the respective parts of a single resin layer of the same composition, distinguished by the degree of crystallinity in the thickness direction, and usually no clear boundary is observed between the two.

[0013] (Molded body morphology) A schematic cross-sectional view of a molded article according to one embodiment of the present invention is shown in Fig. 1. Note that Fig. 1 is merely for illustrating the layer structure of the molded article according to one embodiment, and the aspect ratio and film thickness ratio are not necessarily accurate. As shown in FIG. 1, the molded body 1 includes a molded body main body 2 and a resin sheet 3 (resin layer 31) that covers the molded body main body 2.

[0014] The molded article may be any article that includes a molded body and a resin sheet. The shape of the molded article is not particularly limited, and may be, for example, a layered shape or a specific three-dimensional shape. In one embodiment, when the molded body is layered, the molded body may be a laminate including the layered molded body and a resin sheet. The layer structure of such a laminate is not particularly limited, and may be, for example, a two-layer structure of molded body / resin sheet, or a three-layer structure of resin sheet / molded body / resin sheet. The resin sheet may cover a part of the surface of the molded body, or may cover the entire surface (whole surface) of the molded body.

[0015] The fact that the molded body includes a resin sheet and a molded body can be confirmed, for example, by the fact that the constituent materials or material compositions of the resin sheet and the molded body are different, or by the existence of an interface between the resin sheet and the molded body. The existence of the interface can be confirmed, for example, by cross-sectional observation using a phase contrast microscope or a polarizing microscope. For example, even if the constituent materials or material compositions of the resin sheet and the molded body are the same, the resin sheet and the molded body undergo different molding processes, resulting in different crystalline states, and an interface is formed between the resin sheet and the molded body. Generally, the resin sheet does not contain a fibrous reinforcing material.

[0016] (Main body: Polypropylene) The crystallization rate of the polypropylene used for the molded body at 135°C is 0.6 min -1 Above 0.65min -1 That's it, 0.7min -1 More than 0.75min -1 More than 0.8min -1 That's it, 0.9min -1 That's it, 1.0min -1 That's it, 1.1 minutes -1 or more than 1.2 minutes -1 The upper limit is not particularly limited, and may be, for example, 20 min -1 Below, 15min -1 Below, 10min -1 Below, 8min-1 Below, 6min -1 Below, 5min -1 Below, 4 minutes -1 Less than or equal to 3 minutes -1 It can be the following: The crystallization rate is measured by the method described in the Examples.

[0017] (Main body: fibrous reinforcing material) Examples of fibrous reinforcing materials include inorganic fibers and organic fibers such as glass fibers, carbon fibers, aramid fibers, alumina fibers, boron fibers, and cellulose fibers. These materials may be used alone or in combination of two or more. From the viewpoint of improving the strength of the molded body, glass fibers and carbon fibers are preferred.

[0018] The average fiber length of the fibrous reinforcing material is not particularly limited and may be, for example, 0.1 mm or more, 0.2 mm or more, 0.5 mm or more, or 1 mm or more. The upper limit is not particularly limited and is, for example, 10 mm or less. The fiber length is the length in the longitudinal direction of the fibrous reinforcing material, and the average fiber length is the arithmetic mean value of the fiber lengths measured for 20 reinforcing materials randomly selected from the fibrous reinforcing materials observed in the field of view under a stereomicroscope after burning the resin component of a molded product containing the fibrous reinforcing material in an electric furnace and spreading the remaining fibrous reinforcing material on a preparation or the like.

[0019] The average fiber diameter of the fibrous reinforcing material is not particularly limited and may be, for example, 2 μm or more, 6 μm or more, or 10 μm or more. The upper limit is not particularly limited and is, for example, 100 μm or less. The fiber diameter is the diameter of a circular cross-section reinforcing material, and is the diameter of a perfect circle of the same area when the cross-section is converted into a perfect circle of the same area for reinforcing materials of other cross-section shapes. The average fiber diameter is the arithmetic mean value of the fiber diameters measured for 20 randomly selected reinforcing materials observed in the field of view of a stereomicroscope after burning the resin component of a molded product containing a fibrous reinforcing material in an electric furnace and spreading the remaining fibrous reinforcing material on a preparation or the like.

[0020] The content of the reinforcing fibers in the molded body is not particularly limited, and from the viewpoint of imparting sufficient strength to the molded body, it may be, for example, 7% by mass or more, 10% by mass or more, 12% by mass or more, or 15% by mass or more. The upper limit is not particularly limited, and is, for example, 75% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 38% by mass or less, or 28% by mass or less. The content of the reinforcing fibers relative to the polypropylene used in the molded body is not particularly limited, and may be, for example, 7% by mass or more, 10% by mass or more, 12% by mass or more, or 15% by mass or more. The upper limit is not particularly limited, and may be, for example, 75% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 38% by mass or less, or 28% by mass or less.

[0021] (body: nucleating agent) A nucleating agent may be added to the polypropylene used for the molded body. The crystallization speed of polypropylene can be adjusted by the type and amount of nucleating agent, and the crystallization speed at 135°C can be increased to 0.6 min -1 It can be more than that.

[0022] Specific examples of the nucleating agent include organic carboxylic acids or metal salts thereof, aromatic sulfonic acid salts or metal salts thereof, organic phosphoric acid compounds or metal salts thereof, dibenzylidene sorbitol or derivatives thereof, partial metal salts of rosin acid, inorganic fine particles, imides, amides, quinacridones, quinones, or mixtures thereof.

[0023] Examples of the metal salts of organic carboxylic acids include aluminum benzoate, aluminum pt-butylbenzoate, sodium adipate, sodium thiophenecarboxylate, and sodium pyrrolecarboxylate.

[0024] Examples of dibenzylidene sorbitol or derivatives thereof include dibenzylidene sorbitol, 1,3:2,4-bis(o-3,4-dimethylbenzylidene)sorbitol, 1,3:2,4-bis(o-2,4-dimethylbenzylidene)sorbitol, 1,3:2,4-bis(o-4-ethylbenzylidene)sorbitol, 1,3:2,4-bis(o-4-chlorobenzylidene)sorbitol, 1,3:2,4-dibenzylidene sorbitol, etc. Specific examples include "Gelall MD" and "Gelall MD-R" (trade names) manufactured by New Japan Chemical Co., Ltd.

[0025] Examples of the partial metal salt of rosin acid include "Pine Crystal KM1600", "Pine Crystal KM1500", and "Pine Crystal KM1300" (product names) manufactured by Arakawa Chemical Industries, Ltd.

[0026] Examples of inorganic fine particles include talc, clay, mica, asbestos, glass fiber, glass flakes, glass beads, calcium silicate, montmorillonite, bentonite, graphite, aluminum powder, alumina, silica, diatomaceous earth, titanium oxide, magnesium oxide, pumice powder, pumice balloons, aluminum hydroxide, magnesium hydroxide, basic magnesium carbonate, dolomite, calcium sulfate, potassium titanate, barium sulfate, calcium sulfite, and molybdenum sulfide.

[0027] Examples of the amide compound include adipic acid dianilide and suberic acid dianilide.

[0028] Among the above nucleating agents, it is preferable to use an organic metal phosphate (metal phosphate ester salt) represented by the following general formula, because it is highly effective in increasing the crystallization rate.

[0029] [ka] (In the formula, R 18 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; R 19 and R 20each represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group, an aryl group, or an aralkyl group. M represents any one of an alkali metal, an alkaline earth metal, aluminum, and zinc, and when M is an alkali metal, m represents 0 and n represents 1, when M is an alkaline earth metal or zinc, n represents 1 or 2, when n is 1, m represents 1, when n is 2, m represents 0, and when M is aluminum, m represents 1 and n represents 2.

[0030] Specific examples of organic metal phosphates include "ADK STAB NA-11", "ADK STAB NA-21", and "ADK STAB NA-71" (all manufactured by Asahi Denka Co., Ltd.).

[0031] The amount of nucleating agent in the molded body may be, for example, 0.005% by mass or more, 0.01% by mass or more, 0.05% by mass or more, or 0.1% by mass or more, and may be 4% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, or 0.5% by mass or less.

[0032] (Main body: Other components) The molded body may contain components other than those described above. Examples of the other components include additives such as weather resistance agents and antioxidants, and coloring materials (colorants) such as pigments and dyes.

[0033] (Molded body: composition) 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.8% by mass or more, 99.9% by mass or more, or 100% by mass of the molded body is Polypropylene and fibrous reinforcing materials, or Polypropylene, fibrous reinforcing material, and nucleating agent may be also possible.

[0034] (Resin sheet: resin of resin layer) The resin used for the resin layer is not particularly limited, and examples thereof include polyolefins such as polyethylene (PE), polypropylene (PP), and cyclic polyolefins, polyesters such as polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN), polyamides such as nylon 6 (PA6) and nylon 66 (PA66), polyamideimide (PAI), polymethyl methacrylate (PMMA), polycarbonate (PC), polysulfone (PSF), polyacetal (POM), polyphenylene ether (PPE), polyphenylene sulfide (PPS), polyarylate (PAR), polyetherimide (PEI), polyethersulfone (PES), and polyetherketone (PEK), and may be blended or alloyed resins using two or more of these. Copolymer resins such as AS resin, ABS resin, AES resin, AAS resin, and ACS resin may also be used.

[0035] The resin type used in the resin layer may be the same as or different from that of the molded body. In one embodiment, the resin type used in the resin layer includes polypropylene. Polypropylene is a polymer containing at least propylene. Specific examples include homopolypropylene, copolymers of propylene and olefin, etc. In particular, homopolypropylene is preferred for reasons of heat resistance and hardness. The copolymer may be a block copolymer, a random copolymer, or a mixture thereof. The olefin may be ethylene, butylene, cycloolefin, or the like.

[0036] The polypropylene contained in the resin layer preferably has an isotactic pentad fraction of 80 mol% or more and 99 mol% or less. Such an isotactic pentad fraction may be 80 mol% or more and 98 mol% or less, 86 mol% or more and 98 mol% or less, or 91 mol% or more and 98 mol% or less. When the isotactic pentad fraction is 80 mol % or more, the rigidity of the resin sheet is improved, whereas when the isotactic pentad fraction is 99 mol % or less, the transparency of the resin sheet is improved. The isotactic pentad fraction is the isotactic fraction of a pentad unit (five consecutive propylene monomers isotactically bonded) in the molecular chain of a resin composition. The isotactic pentad fraction is measured by the method described in the Examples.

[0037] The polypropylene contained in the resin layer has a crystallization rate of 2.5 min at 130°C. -1 From the viewpoint of moldability, it is preferable that the above-mentioned range is satisfied. The crystallization rate of the polypropylene contained in the resin layer is 2.5 min -1 Less than 2.0min is preferable. -1 More preferably, the crystallization rate is 2.5 min -1 If the curing time is less than 1 min, the part in contact with the mold can be prevented from hardening rapidly, and the deterioration of the design can be prevented. Although the lower limit is not particularly limited, it is usually 0.1 min -1 That's all. The crystallization rate is measured by the method described in the Examples.

[0038] The crystalline structure of polypropylene preferably contains Smectic crystals. Smectic crystals are a metastable intermediate phase, and each domain size is small, so they are preferred because they have excellent transparency. In addition, since they are metastable, they are preferred because they have excellent moldability, as compared with α crystals, because they soften the sheet with a low amount of heat. The crystalline structure of polypropylene may also include other crystalline forms such as β crystals, γ crystals, and amorphous portions. The polypropylene in the resin sheet may be 30% by mass or more, 50% by mass or more, 70% by mass or more, 85% by mass or more, or 90% by mass or more of smectic crystals.

[0039] The presence or absence of smectic crystals in a resin sheet can be confirmed by the following method. The crystal structure of the polypropylene in the resin sheet is identified by measuring the wide-angle X-ray scattering pattern under the following measurement conditions using an X-ray generator (Rigaku Corporation's "Model Ultra X 18HB") As a result, if a Smectite crystal-type peak is observed even after peak separation, it can be confirmed that Smectite crystals are present in the obtained resin sheet. (Measurement conditions) Light source wavelength: 300mA CuKα line (wavelength = 1.54Å) monochromatic light Line output voltage / current: 50kV / 250mA Irradiation time: 60 minutes Camera length: 1.085m -Sample thickness: Stack the sheets so that they are 1.5 to 2.0 mm. Stack the sheets so that the film formation (MD) direction is aligned. In order to shorten the measurement time, the sheets are overlapped to a distance of 1.5 to 2.0 mm, but if the measurement time is extended, it is possible to measure a single sheet without overlapping.

[0040] When the resin layer contains a polyolefin such as polypropylene, it is preferable that the polyolefin does not contain a nucleating agent. In addition, when the polyolefin does not contain a nucleating agent, it can be said that the resin layer does not contain a nucleating agent. When the nucleating agent is contained, it is preferable that the content is small, for example, 1.0 mass% or less of the resin sheet, preferably 0.5 mass% or less. Examples of the nucleating agent include those described above for the molded body.

[0041] The method for forming the resin layer is not particularly limited, and examples thereof include an extrusion method. The extrusion method includes cooling the molten resin, and the cooling is preferably performed at 80°C / sec or more until the internal temperature of the resin layer becomes equal to or lower than the crystallization temperature. This allows the crystal structure of the polypropylene contained in the resin layer to be a smectic crystal, and the crystallization rate of the polypropylene can be increased to 2.5 min without adding a nucleating agent to the polypropylene. -1 The cooling rate is preferably 90° C. / sec or more, and more preferably 150° C. / sec or more.

[0042] In one embodiment, the crystallization rate of polypropylene without the addition of a nucleating agent is increased to 2.5 min -1 By incorporating the above-mentioned Smectica crystals, a molded product with excellent design can be obtained. In addition, by heating and shaping the resin sheet as described later regarding molding, the resin sheet transitions to α crystals while maintaining the microstructure derived from the Smectica crystals. This transition can further improve the surface hardness and transparency of the molded product surface.

[0043] (Resin sheet: composition of resin layer) In one embodiment, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.8% by mass or more, 99.9% by mass or more, or 100% by mass of the resin layer is resin (polypropylene).

[0044] The thickness of the resin sheet is not particularly limited, but is, for example, 10 μm or more, 50 μm or more, or 150 μm or more, and, for example, 1200 μm or less, 700 μm or less, 500 μm or less, or 350 μm or less.

[0045] (Resin sheet: layer structure) As described above, the resin sheet may form a molded body by covering the molded body with the resin layer alone, or may form a molded body by covering the molded body with the resin layer and one or more other layers in addition to the resin layer. When the resin sheet includes a layer other than the resin layer, the layer other than the resin layer may be disposed on the molded body side as viewed from the resin layer, may be disposed on the opposite side to the molded body, or may be disposed on both sides. In addition, the layer other than the resin layer may be laminated on the entire surface of the resin layer, or may be laminated partially on the resin layer. The same applies when there are multiple layers other than the resin layer, and one layer may be laminated on the entire surface of the other layer, or may be laminated partially.

[0046] Examples of layers other than the resin layer in the resin sheet include an easy-adhesion layer, an undercoat layer, a metal layer, and a printed layer.

[0047] In one embodiment, the resin sheet includes a printed layer on the molded body side as viewed from the resin layer. In one embodiment, the resin sheet includes an easy-adhesion layer on the molded body side as viewed from the resin layer. In one embodiment, the resin sheet includes an undercoat layer on the molded body side as viewed from the resin layer, and includes a metal layer on the molded body side as viewed from the undercoat layer.

[0048] A schematic cross-sectional view of a molded product according to one embodiment in which the resin sheet includes a layer other than the resin layer is shown in Fig. 2. Note that the aspect ratio and film thickness ratio in Fig. 2 are not necessarily accurate. In the molded body 1, the resin sheet 3 covers the molded body 2 as a laminate consisting of a resin layer 31 and four other layers. The resin sheet 3 is a laminate including, from the molded body 2 side, a printed layer 35, a metal layer 34, an undercoat layer 33, an easy-adhesion layer 32, and a resin layer 31 in this order. Each of the other layers is described in more detail below.

[0049] (Easy adhesion layer) The easy-adhesion layer preferably contains one or more resins selected from the group consisting of urethane-based resins, acrylic-based resins, polyolefin-based resins, and polyester-based resins. By providing such an easy-adhesion layer, even if the molded body is molded into a complex non-planar shape, the easy-adhesion layer can conform to the resin sheet to form a good layer structure, thereby preventing cracks and peeling.

[0050] The urethane resin is preferably a urethane resin obtained by reacting a diisocyanate, a high molecular weight polyol, and a chain extender. The high molecular weight polyol may be a polyether polyol or a polycarbonate polyol. Examples of commercially available urethane resins include Hydran WLS-202 (manufactured by DIC Corporation). Examples of acrylic resins include Acrylit 8UA-366 (manufactured by Taisei Fine Chemical Co., Ltd.). An example of the polyolefin resin is Arrowbase DA-1010 (manufactured by Unitika Ltd.). Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate.

[0051] The easy-adhesion layer may use one kind of the above-mentioned materials alone or two or more kinds of them in combination.

[0052] Among the urethane-based resin, acrylic-based resin, polyolefin-based resin and polyester-based resin contained in the easy-adhesion layer, urethane-based resin is preferred in consideration of adhesion to the metal layer and printed layer and formability, which will be described later.

[0053] In addition, when the easy-adhesion layer contains a polypropylene-based resin, the polypropylene-based resin contained in the easy-adhesion layer is usually different from the polypropylene that may be contained in the resin sheet or the molded body.

[0054] The easy-adhesion layer may be made of one or more resins selected from the group consisting of urethane resins, acrylic resins, polyolefin resins, and polyester resins at 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass. For example, the easy-adhesion layer may be a layer made of only a urethane resin.

[0055] The glass transition temperature of the easy-adhesion layer is preferably -100°C or higher and 100°C or lower. When the glass transition temperature is -100°C or higher, the distortion of the easy-adhesion layer does not exceed the conformability of the metal layer and the printing layer described later, so that defects due to cracks do not occur even when used for a long period of time. When the glass transition temperature is 100°C or lower, the softening temperature is appropriate, so that the elongation during pre-shaping is good, and uneven elongation of the stretched part and cracks in the metal layer and the printing layer can be suppressed.

[0056] The glass transition temperature of the easy-adhesion layer can be determined, for example, by measuring a differential scanning calorimetry curve under the following conditions using a differential scanning calorimeter ("DSC-7" manufactured by PerkinElmer Japan Co., Ltd.). Measurement start temperature: -90℃ End of measurement temperature: 220℃ Temperature rise: 10℃ / min

[0057] The tensile elongation at break of the easy-adhesion layer is, for example, 150% or more and 900% or less, preferably 200% or more and 850% or less, and more preferably 300% or more and 750% or less. The tensile elongation at break of the easy-adhesion layer may be 150% or more, 200% or more, or 300% or more, and may be 900% or less, 850% or less, or 750% or less. When the tensile elongation at break of the adhesive layer is 150% or more, the adhesive layer can easily follow the elongation of the resin sheet during thermoforming, and therefore cracking of the adhesive layer, as well as cracking and peeling of the metal layer and the printed layer can be suppressed. When the tensile elongation at break of the adhesive layer is 900% or less, the water resistance is good.

[0058] The tensile elongation at break of the easy-adhesion layer can be evaluated, for example, by applying a resin (composition) having the same composition as that used to form the easy-adhesion layer onto a glass substrate using a bar coater, drying at 80°C for 1 minute, and then separating it to prepare a sample having a thickness of 150 μm, and measuring it according to a method in accordance with JIS K7311:1995.

[0059] The softening temperature of the easy-adhesion layer is, for example, 50° C. or more and 180° C. or less, preferably 90° C. or more and 170° C. or less, and more preferably 100° C. or more and 165° C. or less. The softening temperature of the easy-adhesion layer may be 50° C. or more, 90° C. or more, or 100° C. or more, and may be 180° C. or less, 170° C. or less, or 165° C. or less. When the softening temperature is 50° C. or higher, the adhesive layer has excellent strength at room temperature and can suppress cracking and peeling of the metal layer and the printed layer.When the softening temperature is 180° C. or lower, the adhesive layer is sufficiently softened during thermoforming, so that cracking of the adhesive layer and cracking and peeling of the metal layer and the printed layer can be suppressed.

[0060] The softening temperature of the easy-adhesion layer can be evaluated, for example, by applying a resin (e.g., urethane resin) to be the easy-adhesion layer onto a glass substrate using a bar coater, drying at 80°C for 1 minute, and then separating it to create a sample with a thickness of 150 μm, and measuring the flow start temperature using a high-speed flow tester (Shimadzu Corporation's ``Constant Test Force Extrusion Type Capillary Rheometer Flow Tester CFT-500EX'').

[0061] The easy-adhesion layer may be a single layer alone or may have a laminated structure of two or more layers.

[0062] The thickness of the easy-adhesion layer may be 35 nm or more and 3000 nm or less, 50 nm or more and 2000 nm or less, or 50 nm or more and 1000 nm or less. The thickness of the easy-adhesion layer may be 35 nm or more, or 50 nm or more, and may be 3000 nm or less, 2000 nm or less, or 1000 nm or less.

[0063] The easy-adhesion layer can be formed, for example, by applying the above-mentioned resin with a gravure coater, a kiss coater, a bar coater, or the like, and drying it at 40 to 100° C. for 10 seconds to 10 minutes.

[0064] On the adhesive layer, various coatings such as ink, hard coat, anti-reflection coat, and heat-shielding coat can be laminated. In addition, in the resin sheet, another easy-adhesion layer (second easy-adhesion layer) may be provided on the surface opposite to the easy-adhesion layer (first easy-adhesion layer). In this way, functionality such as surface treatment and hard coating can be imparted to the polyolefin resin layer that becomes the surface of the molded product.

[0065] (Undercoat layer) The undercoat layer is a layer that can bond the easy-adhesion layer and the metal layer to each other. By providing the undercoat layer, even if stress is applied during thermoforming, countless extremely fine cracks can be generated in the metal layer, and the occurrence of the rainbow phenomenon can be eliminated or reduced. Examples of materials for forming the undercoat layer include urethane resins, acrylic resins, polyolefins, and polyesters.

[0066] From the viewpoints of whitening resistance during molding (how little whitening occurs) and adhesion to the metal layer, the material for forming the undercoat layer is preferably an acrylic resin, and for example, "DA-105" manufactured by Arakawa Chemical Industries, Ltd. can be used.

[0067] The above materials may be used alone or in combination of two or more.

[0068] In the undercoat layer, the above-mentioned resin component (main agent) may be used in combination with a curing agent. Examples of the curing agent include aziridine compounds, blocked isocyanate compounds, epoxy compounds, oxazoline compounds, carbodiimide compounds, etc., and for example, "CL102H" manufactured by Arakawa Chemical Industries, Ltd. can be used.

[0069] When a curing agent is used, the content ratio of the main agent to the curing agent in the undercoat layer is, for example, 35:4 to 35:40, preferably 35:4 to 35:32, more preferably 35:12 to 35:32, in terms of the mass ratio of solid contents, and may also be 35:12 to 35:20. When the ratio of the hardener to the base resin is 35 to 4 or more, the hardening reaction proceeds smoothly and whitening resistance can be maintained. When the ratio is 40 or less, the extensibility of the undercoat layer is good and cracks during molding can be suppressed.

[0070] The undercoat layer can be formed, for example, by applying the above-mentioned material with a gravure coater, kiss coater, bar coater, or the like, drying at 50 to 100°C for 10 seconds to 10 minutes, and aging at 40 to 100°C for 10 to 200 hours.

[0071] The thickness of the undercoat layer may be 0.05 μm to 50 μm, may be 0.1 μm to 10 μm, or may be 0.5 μm to 5 μm. The thickness of the undercoat layer may be 0.05 μm or more, 0.1 μm or more, or 0.5 μm or more, and may be 50 μm or less, 10 μm or less, or 5 μm or less.

[0072] (metal layer) The metal layer is a layer containing a metal or a metal oxide. The metal for forming the metal layer is not particularly limited as long as it is a metal that can impart a metallic design to the laminate, and examples thereof include tin, indium, chromium, aluminum, nickel, copper, silver, gold, platinum, and zinc. An alloy containing at least one of these metals may also be used. Among the above, indium and aluminum are preferable because they are particularly excellent in terms of ductility and color tone. When the metal layer has excellent ductility, cracks are less likely to occur when the laminate is three-dimensionally molded.

[0073] The method for forming the metal layer is not particularly limited, but from the viewpoint of imparting a high-quality, luxurious metallic design to the laminate, for example, a deposition method using the above-mentioned metals, such as a vacuum deposition method, a sputtering method, or an ion plating method, can be used. In particular, the vacuum deposition method is low cost and can reduce damage to the deposition target. The conditions for the vacuum deposition method may be appropriately set according to the melting temperature or evaporation temperature of the metal used.

[0074] In addition to the above-mentioned methods, a method of applying a paste containing the above-mentioned metal or metal oxide, a plating method using the above-mentioned metal, etc. can also be used.

[0075] The thickness of the metal layer may be 5 nm or more and 80 nm or less. If it is 5 nm or more, the desired metallic luster can be obtained without any problems, and if it is 80 nm or less, cracks are unlikely to occur.

[0076] (Printing layer) The shape of the printed layer is not particularly limited, but may be, for example, a solid shape, a carbon pattern, a wood grain pattern, or the like. As the printing method, general printing methods such as screen printing, offset printing, gravure printing, roll coating, spray coating, etc. In particular, screen printing can make the ink film thick, so ink cracks are less likely to occur when the product is molded into a complex shape. For example, in the case of screen printing, inks that have excellent elongation during molding are preferred, and examples thereof include "FM3107 High Density White" and "SIM3207 High Density White" manufactured by Jujo Chemical Co., Ltd., but are not limited to these.

[0077] (Method of Manufacturing Molded Product) The method for producing the above-described molded article is not particularly limited. In one embodiment, a molded body can be produced by injection molding a composition for forming a molded body body (a molding resin composition) on a resin sheet. Specific examples of the molding method include in-mold molding and insert molding.

[0078] (In-mold molding) In one embodiment, a method for producing a molded article is a method for producing a molded article according to one aspect of the present invention described above, comprising the steps of: placing a resin sheet on a mold; and forming a molded article having a crystallization rate of 0.6 min at 135° C. -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the resin sheet, and the resin sheet is shaped to fit a mold while being integrated with the molding resin composition. Here, the molding resin composition is cooled and solidified on the resin sheet to form a molded body. In such a method for producing a molded article (in-mold molding method), a resin sheet is placed in a mold and molded into a desired shape by the pressure of a molding resin composition supplied into the mold, thereby obtaining a molded article.

[0079] (insert molding) In another embodiment, the method for producing a molded article is a method for producing a molded article according to one aspect of the present invention described above, comprising forming a resin sheet to fit a mold and forming the molded article into a mold having a crystallization rate of 0.6 min at 135° C. -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the shaped resin sheet, and the molding resin composition and the resin sheet are integrated together. Here, the molding resin composition is cooled and solidified on the resin sheet to form a molded body. In such a manufacturing method for a molded body (insert molding method), a molded body can be obtained by preforming a shaped body (resin sheet) to be placed in a mold and filling the molding resin composition according to the shape of the preform. In insert molding, molded bodies with more complicated shapes can be formed compared to the above-mentioned in-mold molding. Shaping (pre-shaping) to fit a mold can be performed by vacuum forming, pressure forming, vacuum pressure forming, press forming, plug assist forming, etc. When shaping, the resin sheet can be heated in advance.

[0080] A method for producing a molded article according to one embodiment of the present invention includes heating a molding resin composition containing polypropylene and a fibrous reinforcing material so that the polypropylene melts, supplying the heated molding resin composition onto a resin sheet arranged in a mold, and cooling and solidifying the molding resin composition on the resin sheet to obtain a molded article including a molded body made of the solidified molding resin composition and the resin sheet covering at least a part of the surface of the molded body. The crystallization rate of the polypropylene contained in the molding resin composition subjected to melting at 135°C is 0.6 min -1 That's all.

[0081] (Use of Molded Body) The applications of the molded article described above are not particularly limited, and the molded article can be used for various applications. In one embodiment, the molded article can be used as an exterior part of a saddle-type vehicle or an exterior part of a four-wheeled vehicle. The molded article can also be used as an interior material, an exterior material, a housing for home appliances, a decorative steel plate, a decorative plate, a housing for housing equipment, a housing for information and communication devices, and the like. EXAMPLES

[0082] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0083] Example 1 (1) Manufacturing of resin sheets A resin sheet was manufactured using the device shown in Fig. 3. Polypropylene (Prime Polypro F133A manufactured by Prime Polymer Co., Ltd., hereinafter sometimes referred to as "PP-1") was used as the raw material for the resin sheet. The operation of this device will be described. Molten polypropylene resin extruded from a T-die 52 of an extruder is sandwiched between a metallic endless belt 57 and a fourth cooling roll 56 on a first cooling roll 53. In this state, the molten resin is pressed against the first and fourth cooling rolls 53 and 56 and rapidly cooled to form a resin sheet. The resin sheet is then sandwiched between the metallic endless belt 57 and the fourth cooling roll 56 at a circular arc portion corresponding to the approximately lower half of the fourth cooling roll 56 and pressed against each other. After being pressed against each other and cooled by the fourth cooling roll 56, the resin sheet in close contact with the metallic endless belt 57 is moved onto the second cooling roll 54 as the metallic endless belt 57 rotates. As described above, the resin sheet is pressed against the metallic endless belt 57 at a circular arc portion corresponding to the approximately upper half of the second cooling roll 54 and is cooled again. The resin sheet 51 cooled on the second cooling roll 54 is then peeled off from the metallic endless belt 57. The surfaces of the first and second cooling rolls 53 and 54 are covered with an elastic material 62 made of nitrile-butadiene rubber (NBR). The third cooling roll 55 also functions to support and rotate the metallic endless belt 57 from below. The manufacturing conditions for the resin sheet are as follows. Extruder diameter: 75mm Width of T-die 52: 900mm Thickness: 200μm Take-up speed of resin sheet 51: 4.5 m / min Surface temperature of the fourth cooling roll 56 and the metal endless belt 57: 20°C ·Cooling rate: 8,100℃ / min

[0084] (2) Crystallization rate of polypropylene in resin sheet (crystallization rate at 130°C) The crystallization rate of the polypropylene used in the resin sheet was measured using a differential scanning calorimeter (DSC) (PerkinElmer's "Diamond DSC"). Specifically, a piece taken from the resin sheet was heated from 50°C to 230°C at 80°C / min, held at 230°C for 5 minutes, cooled from 230°C to 130°C at 80°C / min, and then held at 130°C to crystallize the polypropylene. Measurement of the change in heat quantity was started when the temperature reached 130°C, and a DSC curve was obtained. The crystallization rate was calculated from the obtained DSC curve by the following steps (i) to (iv). (i) The baseline was determined by approximating the change in heat quantity from a point 10 times the time from the start of measurement to the peak top to a point 20 times the time by a straight line. (ii) The intersection points between the tangent line having a slope at the inflection point of the peak and the baseline were determined, and the crystallization start and end times were calculated. (iii) The time from the obtained crystallization start time to the peak top was measured as the crystallization time. (iv) The crystallization rate was calculated from the reciprocal of the obtained crystallization time.

[0085] (3) Isotactic pentad fraction of polypropylene in resin sheet 13The isotactic pendant fraction of the polypropylene in the resin sheet was measured by evaluating the C-NMR spectrum. Specifically, the peak assignments proposed by A. Zambelli et al. in "Macromolecules, 8, 687 (1975)" were followed using the following equipment, conditions, and calculation formula. As a result, the isotactic pendant fraction of the resin sheet was 98 mol%. (equipment / conditions) Device: 13 C-NMR device (JNM-EX400, manufactured by JEOL Ltd.) Method: Proton complete decoupling method (concentration: 220 mg / ml) Solvent: 90:10 (volume ratio) mixture of 1,2,4-trichlorobenzene and heavy benzene Temperature: 130℃ Pulse width: 45° Pulse repetition time: 4 seconds Accumulation: 10,000 times (calculation formula) Isotactic pendant fraction [mmmm] = m / S × 100 (In the formula, S represents the signal intensity of the side chain methyl carbon atom of all propylene units, and m represents a meso pentad chain (21.7 to 22.5 ppm).)

[0086] (4) Preparation of molding resin composition A molding resin composition was prepared by adding a master batch containing a phosphate metal salt as a nucleating agent (ADEKA STAB NA-11 manufactured by ADEKA CORPORATION, hereinafter sometimes referred to as "phosphate metal salt-1") to short glass fiber reinforced polypropylene (Prime Polypro V7100 manufactured by Prime Polymer Co., Ltd., glass fiber content 20 mass% (average fiber length: 0.3 mm, average fiber diameter (diameter): 0.013 mm), hereinafter sometimes referred to as "fiber reinforced PP-1") so that the concentration of the phosphate metal salt relative to the total amount of the composition was 1500 ppm. When adding the above, mixing was performed by dry blending.

[0087] (5) Manufacturing of Molded Products The resin sheet obtained in (1) was cut to 100 mm x 100 mm and attached to the fixed cavity surface of a flat plate-shaped mold (125 mm x 125 mm, thickness 2 mm), and the molding resin composition obtained in (4) was fed into the mold using a hydraulic injection molding machine ("IS-80EPN" manufactured by Toshiba Machine Co., Ltd.) to integrate the components to obtain a molded product. At this time, the temperature of the molding resin composition fed into the mold was 230°C, and the mold temperature was 50°C.

[0088] (6) Measurement of crystallization rate of polypropylene in molding resin composition (crystallization rate at 135°C) Using a differential scanning calorimeter (DSC) (PerkinElmer's "Diamond DSC"), the crystallization rate of polypropylene of the molding resin composition (containing short glass fiber reinforced polypropylene and a nucleating agent) sampled from the molded body in the molded product was measured. Specifically, the molding resin composition was heated from 50°C to 230°C at 80°C / min, held at 230°C for 5 minutes, cooled from 230°C to 135°C at 80°C / min, and then held at 135°C to crystallize the polypropylene. Measurement of the change in heat quantity was started when the temperature reached 135°C, and a DSC curve was obtained. From the obtained DSC curve, the crystallization rate was obtained by the following steps (i) to (iv). (i) The baseline was determined by approximating the change in heat quantity from a point 10 times the time from the start of measurement to the peak top to a point 20 times the time by a straight line. (ii) The intersection points between the tangent line having a slope at the inflection point of the peak and the baseline were determined, and the crystallization start and end times were calculated. (iii) The time from the obtained crystallization start time to the peak top was measured as the crystallization time. (iv) The crystallization rate was calculated from the reciprocal of the obtained crystallization time.

[0089] (7) Maximum height of the molded body surface Rz The molded product obtained in (5) was measured for the surface shape in the direction perpendicular to the flow direction on the molded product surface (resin sheet surface) using a "Handysurf E-35B" manufactured by Tokyo Seimitsu Co., Ltd. in accordance with JIS B 0601:2001 under the following measurement conditions. The distance between the crest line and the valley line in the cross-sectional curve obtained in this manner was taken as the maximum height Rz. The results are shown in Table 1. <Measurement conditions> Measurement distance: 10mm Cutoff: None Stylus: Tip diameter 5μm, tip accuracy 90° cone, material diamond ·Measuring force: 4mN or less

[0090] (8) Glossiness For the molded article obtained in (5), a glossmeter ("VG7000" manufactured by Nippon Denshoku Industries Co., Ltd.) was used to irradiate light from the resin sheet surface of the molded article at an incident angle of 60 degrees in accordance with the 60-degree specular gloss measurement method of JIS Z 8741:1997, and the reflected light flux ψs was measured when the reflected light was received at the same 60 degrees. The gloss was calculated from the ratio of this to the reflected light flux ψ0s from a glass surface with a refractive index of 1.567 using the following formula (1). The results are shown in Table 1. Glossiness (Gs) = (ψs / ψ0s) * 100 (1)

[0091] Example 2 A molded article was produced and evaluated in the same manner as in Example 1, except that a phosphate metal salt ("ADEKA STAB NA-21" manufactured by ADEKA CORPORATION, hereinafter sometimes referred to as "phosphate metal salt-2") was used as the nucleating agent for the molding resin composition instead of the phosphate metal salt-1 in Example 1. The results are shown in Table 1.

[0092] Example 3 A molded article was produced and evaluated in the same manner as in Example 1, except that a phosphate metal salt ("ADEKA STAB NA-71" manufactured by ADEKA CORPORATION, hereinafter sometimes referred to as "phosphate metal salt-3") was used as the nucleating agent for the molding resin composition instead of the phosphate metal salt-1 in Example 1. The results are shown in Table 1.

[0093] Example 4 A molded article was produced and evaluated in the same manner as in Example 3, except that the nucleating agent, phosphoric acid ester metal salt 3, was added in an amount of 3000 ppm relative to the total amount of the molding resin composition. The results are shown in Table 1.

[0094] Example 5 In Example 4, except that short glass fiber reinforced polypropylene ("Mostron L-4040P" manufactured by Prime Polymer Co., Ltd., glass fiber content 40 mass% (average fiber length: 1.0 mm, average fiber diameter (diameter): 0.015 mm), hereinafter sometimes referred to as "fiber reinforced PP-2") was used instead of fiber reinforced PP-1, a molded body was produced and evaluated in the same manner as in Example 4. The results are shown in Table 1.

[0095] Comparative Example 1 Except for not adding a nucleating agent to the molding resin composition, a molded article was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0096] Comparative Example 2 Except for not adding a nucleating agent to the molding resin composition, a molded article was produced and evaluated in the same manner as in Example 5. The results are shown in Table 1.

[0097] [Table 1]

[0098] From Table 1, it can be seen that the molded body of the present invention has high surface smoothness and excellent appearance. The maximum height Rz of Example 5 is larger than that of Comparative Example 1, but this is because the maximum height Rz is highly dependent on the physical properties (particularly fiber length) and content of the fibrous reinforcing material contained in the molded body. Since Example 5 contains a large amount of fibrous reinforcing material with long fiber length, the Rz value is high, but compared to Comparative Example 2 (wherein the conditions other than the nucleating agent are the same), Rz is significantly lower, which shows the effect of improving the surface smoothness of the molded body by specifying the crystallization rate of the polypropylene constituting the molded body.

[0099] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.

Claims

1. A molded body including polypropylene and a fibrous reinforcing material; A resin sheet including at least a resin layer and covering at least a part of a surface of the molded body; Including, The crystallization rate of the polypropylene at 135°C is 1.25 min -1 The above is a molded body.

2. The molded article according to claim 1 , wherein the resin layer in the resin sheet contains polypropylene.

3. The crystallization rate of the polypropylene contained in the resin layer at 130° C. is 2.5 min -1 The molded body according to claim 2, wherein:

4. The molded article according to claim 2 or 3, wherein the polypropylene contained in the resin layer has an isotactic pentad fraction of 80 mol % or more and 99 mol % or less.

5. The molded body according to any one of claims 2 to 4, wherein the content of the nucleating agent for the polypropylene contained in the resin layer is 1.0 mass% or less of the resin layer.

6. The molded article according to any one of claims 2 to 5, wherein the polypropylene contained in the resin layer does not contain a nucleating agent.

7. The molded body according to any one of claims 1 to 6, wherein the resin sheet includes a printing layer on the molded body side as viewed from the resin layer.

8. The resin sheet includes an easy-adhesion layer on the molded body side as viewed from the resin layer, The molded body according to any one of claims 1 to 7, wherein the easy-adhesion layer comprises one or more selected from the group consisting of urethane resins, acrylic resins, polyolefins, and polyesters.

9. The resin sheet includes an undercoat layer located on the molded body side as viewed from the resin layer, and a metal layer laminated on the molded body side as viewed from the undercoat layer, the undercoat layer comprises one or more resins selected from the group consisting of urethane resins, acrylic resins, polyolefins, and polyesters, The molded body according to any one of claims 1 to 8, wherein the metal layer contains one or more metal elements selected from the group consisting of tin, indium, chromium, aluminum, nickel, copper, silver, gold, platinum and zinc.

10. Placing a resin sheet on the mold; and Crystallization speed at 135°C is 1.25 min -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the resin sheet, and the resin sheet is shaped to fit a mold while the molding resin composition and the resin sheet are integrated. The method for producing the molded body according to any one of claims 1 to 9, comprising:

11. Shaping the resin sheet to fit the mold; and Crystallization speed at 135°C is 1.25 min -1 The molding resin composition containing the polypropylene and the fibrous reinforcing material is supplied onto the shaped resin sheet, thereby integrating the molding resin composition with the resin sheet. The method for producing the molded body according to any one of claims 1 to 9, comprising:

12. Heating a molding resin composition containing polypropylene and a fibrous reinforcing material so that the polypropylene melts; Supplying the heated molding resin composition onto a resin sheet placed in a mold; and The molding resin composition is cooled and solidified on the resin sheet to obtain a molded body including a molded body main body made of the solidified molding resin composition and the resin sheet covering at least a part of a surface of the molded body. Including, The crystallization rate of the polypropylene contained in the molding resin composition subjected to the melting at 135° C. is 1.25 min -1 That's all. A method for producing a molded body.

Citation Information

Patent Citations

  • Composite molding method for molded item of resin and item of resin molded by composite molding

    JP2000117759A

  • Fiber-reinforced decorated molding and its manufacture

    JP2000158481A

  • Laminated resin molded object

    JP2010260251A

  • Decorative molding and method for producing the same

    JP2018144476A

  • Aluminum composite material, composite structure and its manufacturing method

    JP2018171933A